2014
DOI: 10.2341/11-495-l
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Four Lining Materials in Sandwich Technique to Reduce Microleakage in Class II Composite Resin Restorations

Abstract: The sandwich technique results in more microleakage than classically bonded composite resin restorations. SUMMARYObjectives: The aim of the present study was to evaluate the effect of four different sandwich techniques on gingival microleakage of Class II direct composite resin restorations. Materials and Methods: Fifty sound human premolars were selected and randomly divided into five groups (n=10). Class II box only cavities were prepared in one of the proximal surfaces of each tooth with a gingival margin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…However, the above observations of polyacrylic acid are relevant to the clinical dilemma of whether to directly "bond" a composite restoration in deep cavities or to "base" it with glass ionomer cement. Evidence is currently inconclusive on the comparative superiority of the sandwich technique versus direct composite resin restorations for microleakage control (Kasraei et al 2011;Gungor et al 2014;Moazzami et al 2014). Our findings highlight an important aspect where potential differences exist between the 2 techniques, shifting the balance against the apparently inert glass ionomer system in situations where inducing a reparative response is crucial for the treatment success.…”
Section: Discussionmentioning
confidence: 67%
“…However, the above observations of polyacrylic acid are relevant to the clinical dilemma of whether to directly "bond" a composite restoration in deep cavities or to "base" it with glass ionomer cement. Evidence is currently inconclusive on the comparative superiority of the sandwich technique versus direct composite resin restorations for microleakage control (Kasraei et al 2011;Gungor et al 2014;Moazzami et al 2014). Our findings highlight an important aspect where potential differences exist between the 2 techniques, shifting the balance against the apparently inert glass ionomer system in situations where inducing a reparative response is crucial for the treatment success.…”
Section: Discussionmentioning
confidence: 67%
“…Although different techniques have been used to evaluate microleakage ( 16 , 17 ), the dye penetration method was selected for the present study. Although, the semi quantitative dye penetration technique was widely accepted method for in vitro studies, clinical relevance was questioned in a recent systematic review ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Koubi et al ( 24 ) observed that in open sandwich restorations, resin modified glass ionomer material, Fuji II LC was the best intermediate material. However, Moazzami et al ( 16 ) evaluated the effect of different materials (resin modified glass ionomer, compomer and self-curing resin, flowable composite resin) on the gingival microleakage of Class II open sandwich restorations. As a result, none of the materials enhanced the microleakage scores.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the traditional sandwich technique using resin-modified glass ionomer cement with resin composite leads to more leakage than that using flowable resin composite does. 32 Therefore, we covered the resin-modified glass ionomer cement liner and the floor of the cavity with a layer of flowable resin composite. Flowable composites showed more stress-buffering capacity and an improved marginal seal than hybrid resin composites did.…”
Section: Discussionmentioning
confidence: 99%